Osiągnięcia szkolne czwartoklasistów w oddziałach o różnym składzie wiekowym - Krzysztof Konarzewski (Problemy Wczesnej Edukacji)
Are hopes pinned on mixed-age grouping in preschool and elementary school substantiated by scientific data? The answer was looked for in TIMSS 2015 research in Poland. It was carried on in the middle of the reform of school entry age which lowered it from seven to six year of life. In the country representative sample of fourth-graders 17.8 percent of pupils entered school at the age of six. In 254 classrooms the dispersion of age varied from 0.20 to 0.65 years and was greater than in TIMSS 2011 (0.15–0.40). The analysis of achievement in mathematics and science was performer by means of hierarchical linear models with the control of pupils’ gender, age, initial skills, and SES, as well as school’s location and class size. The achievement in mathematics was correlated significantly negative with the dispersion of age in the class. The younger pupils scored the highest in mathematics and science in classes with moderate dispersion. The results do not support a belief that mixed-age grouping is beneficial to academic achievement.